Effects of Carpal Tunnel Syndrome on adaptation of multi-digit forces to object texture - Afifi, Mostafa (2012)
OBJECTIVE: The ability to adapt digit forces to object properties requires both anticipatory and feedback-driven control mechanisms which can be disrupted in individuals with a compromised sensorimotor system. Carpal Tunnel Syndrome (CTS) is a median nerve compression neuropathy affecting sensory and motor function in a subset of digits in the hand. Our objective was to examine how CTS patients coordinate anticipatory and feedback-driven control for multi-digit grip force adaptation. METHODS: We asked CTS patients and healthy controls to grasp, lift, and hold an object with different textures. RESULTS: CTS patients effectively adapted their digit forces to changes in object texture, but produced excessive grip forces. CTS patients also produced larger peak force rate profiles with fewer modulations of normal force prior to lift onset than did controls and continued to increase grip force throughout the lift whereas forces were set at lift onset for the controls. CONCLUSIONS: These findings suggest that CTS patients use less online sensory feedback for fine-tuning their grip forces, relying more on anticipatory control than do healthy controls. SIGNIFICANCE: These characteristics in force adaptation in CTS patients indicate impaired sensorimotor control which leads to excessive grip forces with the potential to further exacerbate their median nerve compression.